Ultrasonographic assessment of ocular parameters in dogs: effects of weight and breed, controlled for BCS and age - Kim, Yourang; Kim, Bumseok; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2024)
IntroductionOphthalmic ultrasound is useful tool for examining canine eyes. Previous studies have compared ocular parameters using ophthalmic ultrasonography based on body weight, breed, sex, and age. However, there are limited studies involving large numbers of dogs with controlled body condition score. Furthermore, to the authors' knowledge, there are no established parameters that can be used independently of body weight. The aim of this study was (1) to compare ultrasonography ocular parameters based on body weight, breed, sex, and age in dogs with an ideal body condition score, (2) to establish normal reference ranges for ultrasonography ocular parameters on a large number of samples, (3) to establish an ultrasonography ocular parameter ratio that can be used regardless of body weight.MethodsA total of 225 dogs were collected, of which 120 dogs without abnormalities on ophthalmologic and clinical examinations were included according to the inclusion criteria. The ocular parameters measured were the anterior chamber (AC), vitreous chamber (VC), lens axial length (LAL), lens equatorial length (LEL), and globe axial length (GAL).ResultsIn LEL and GAL, a strong positive correlation was observed with body weight, and significant differences were identified between all body weight groups (p < 0.05). The mean LEL for each body weight groups is as follows: 1 ≤ body weight < 5 kg; 1.118 ± 0.032 cm, 5 ≤ body weight < 10 kg; 1.17 ± 0.03 cm, 10 ≤ body weight < 20 kg; 1.218 ± 0.018 cm, 20 ≤ body weight < 35 kg; 1.313 ± 0.03 8cm (R2 = 0.820; β = 0.008; p < 0.001). The mean GAL for each body weight groups is as follows: 1 ≤ body weight < 5 kg; 1.731 ± 0.076 cm, 5 ≤ body weight < 10 kg; 1.841 ± 0.064 cm, 10 ≤ body weight < 20 kg; 1.915 ± 0.043 cm, 20 ≤ body weight < 35 kg; 2.027 ± 0.059 cm (R2 = 0.598; β = 0.012; p < 0.05). The positive correlation with body weight was weaker for the AC, VC, and LAL than for the LEL and GAL. No significant differences were found among breeds, sexes, or ages, nor between the left and right eyes in all ocular parameters (p > 0.05). And we found that LEL:GAL ratio has no correlation with body weight (0.642 ± 0.022; R2 = −0.006; β = 0.000; p > 0.05).DiscussionThis study identified significant correlations between LEL, GAL, and body weight in dogs with ideal body condition. We established normal reference ranges for ocular parameters within each BW group and breed based on a large number of samples. In addition, we present the LEL:GAL ratio, which is a constant value regardless of body weight or breed, as expected to be clinically useful in ocular evaluation.